Solvothermal Systhesis of Size‐Controlled Porous Co3O4 Nanostructure Catalyst and Their Catalytic Properties for VOCs Removal. Issue 37 (5th October 2018) - Zhao, Jiuhu; Han, Weiliang; Dong, Fang; Zhang, Jiyi; Tang, Zhicheng
Abstract: Porous Co3 O4 nanocatalysts with tunable size were fabricated by solvothermal method using different solvent, such as ethanol, ethylene glycol and water, respectively. After that, the Pd was successfully loaded on the Co3 O4 precursor by impregnation method to obtain Pd/Co3 O4 catalysts, which were used in toluene total oxidation. The catalyst prepared with ethanol as solvent (Pd/Co3 O4 ‐E) exhibited excellent catalytic performance and the total conversion temperature (T100 ) was 200 °C at a weight hourly space velocity of 21000 h −1 . The influence factors for the performance of the catalysts were characterized by a series of techniques. The SEM, TEM and XRD results of Pd/Co3 O4 catalysts displayed the different structure by using different solvent and the Pd/Co3 O4 ‐E exhibited the largest size about 13.6 nm. The BET surface area, surface adsorbed oxygen of the Pd/Co3 O4 leaded to the superior activity for toluene total oxidation. The catalytic performance of Pd/Co3 O4 catalysts was also associated with the effect of BET surface area of Co3 O4 support on Pd dispersion, surface active oxygen and the interaction between Pd nanoparticles and Co3 O4 . Abstract : Different nanoparticles sizes of Co3 O4 were fabricated via the solvothermal method, and Pd/Co3 O4 catalyst was successfully fabricated by impregnation methods for the removal of toluene. The Pd nanoparticles were uniformly dispersed on the surface of the Co3 O4 sample. The Pd/Co3 O4 catalyst prepared with ethanol as solvent exhibits an unexpected, surprisingly high catalytic activity.